Effect of cage and pen housing on the live performance, carcase, and meat quality traits of growing rabbits. Issue 1 (2nd January 2019) - Matics, Zsolt; Cullere, Marco; Zotte, Antonella Dalle; Szendrő, Katalin; Szendrő, Zsolt; Odermatt, Meinrad; Atkári, Tamás; Radnai, István; Nagy, István; Gerencsér, Zsolt
Abstract: The aim of the experiment was to study the effect of housing growing rabbits in enriched cages with small groups (eight rabbits/cage, C; n =  96; stocking density: 15 rabbits/m 2 ) or in enriched pens with large groups (65 rabbits/pen, P; n =  130; stocking density: 15 rabbits/m 2 ) on their growth performance and on slaughter and meat quality traits. The C rabbits showed higher final body weight (2540 vs. 2443 g, p <  .01), better feed conversion ratio (5–11 weeks: 3.39 vs. 3.61, p <  .05), lower mortality rate (5.2 vs. 31.5%, p <  .001), and lower fecal corticosterone level (26.3 vs. 29.4 nmol/g, p <  .05) compared to P rabbits. The increased possibility of physical activity of P compared to C rabbits resulted in more developed hind part of the reference carcase, thicker hind leg bones (34.8 vs. 33.4 g, p <  .05), lower perirenal fat (15.1 vs. 20.8 g, p <  .001) and hind leg meat lipid content (2.00 vs. 2.42%, p <  .05), as well as higher haem iron content of the hind leg meat (5.29 vs. 4.22 mg/kg, p <  .01). However, pen housing was detrimental for the dressing out percentage and for the hind leg meat to bones ratio. Physical meat quality traits were not affected by the housing system. Highlights: Housing of growing rabbits in large cages and large pens was compared. Caged rabbits had better productive performance, lower mortality and stress. Penned rabbits resulted in lower dressing out percentage, carcase adiposity and meat lipids content. Most of the meat quality traits were independent of the housing system.